Hydrological impact of small hydropower development on mountain rivers in Southwest China and the role of environmental flows - Li,X; Buytaert,W; Tang,Q; Wang,Y; Liang,R; Li,K (Journal of Hydrology, 2025)
Small- and medium-sized mountain rivers are often the locations of small hydropower plants (SHPs), which bring electricity to remote mountainous areas but also cause a range of environmental and ecological impacts. Alterations in hydrological regimes are the most direct impact of SHPs, which in turn triggers changes in physical, chemical, and biological conditions. Environmental agencies of many countries have taken measures to mitigate hydrological changes in these rivers, including requiring SHPs to release environmental flows. However, it remains unclear how effective these measures are in compensating for hydrological changes. In this study, we examined hydrological alterations in seven small mountain river basins in the Yangtze River using a combination of numerical simulation and statistical analysis. A framework was presented and applied to assess the impacts of SHPs and the effects of environmental flows. A total of 32 hydrological indicators were selected and calculated based on measured and modeled hydrological data, and the changes in these indicators were assessed using three indexes. The values of extreme and dynamic water conditions indicators were significantly changed after the SHPs were fully developed. Five indicators, including the number of low pulses, the number of high pulses, the duration of low pulses, the daily rise rate, and the number of flow reversals, were identified as the most unfavorable indicators. A constant environmental flow release of 10% of the long-term average flow, which is the current policy, had a limited impact on mitigating adverse hydrological changes. We therefore suggest the development of an environmental flow regime that better mimics natural flow variability, but not just based on a constant release threshold in small hydropower-developed rivers.